Ischemic mitral regurgitation: modern evidence based echocardiography diagnosis, quantification and risks stratification review - Rudenko, S. A.; Potashev, S. V.; Hrubiak, L. M.; Mazur, O. A.; Gogayeva, O. K.; Rudenko, A. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Ischemic mitral regurgitation (IMR) is a frequent complication in the patients after acute myocardial infarction (AMI) or in ischemic cardiomyopathy (ICM), associated with significant prognosis worsening. Mitral valve (MV) involvement may be primary (organic MR) or secondary (functional MR). Primary MR develops because of mitral subvalvular apparatus rupture as an AMI complication. Secondary IMR develops in the conditions of normal MV cusps and chords structure because of balance impairment between MV closure and tension forces secondary to left ventricle (LV) geometry alterations. According to evidence data both scenarios of IMR are associated with at least one major coronary artery critical stenosis (>70%). Secondary IMR is the most frequent consequence of ischemic cardiomyopathy. IMR diagnosis is associated with elevated patients mortality compared to those without it. It has been shown, that survival within patients with IMR after AMI down to 40% in case of moderate-to-severe IMR, compared to 62% in the patients with mild IMR or 84% in the patients without IMR at all. Pathophysiological mechanisms of IMR are not fully understood, but it is well known, that IMR is a complex entity, having left chambers, especially left ventricle (LV) remodeling as a key cause. Echocardiography (EchoCG) significantly contributes to understanding the underlying mechanisms of IMR. The aim of this review is to summarize modern evidence based data about IMR mechanisms and analysis of contemporary EchoCG indices for diagnosis, evaluation and risks stratification in the patients with IMR. IMR develops in approximately 20% of patients after AMI with increasing occurrence over past years, significantly influencing patients’ prognosis. IMR is a complex and dynamic entity, where LV remodeling is the main factor of MV dysfunction. EchoCG plays the clue role in IMR diagnosis giving the detailed information about its mechanisms and severity grading. Comprehensive EchoCG in the patients with coronary arteries disease (CAD) allows a better and comprehensive approach in risks stratification and optimal surgical IMR treatment planning.